2003
DOI: 10.1176/jnp.15.4.436
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Stressful Life Events and Cognitive Function in HIV-Infected Men

Abstract: Previous studies have demonstrated an impact of stress on immune function, and recent studies have suggested an adverse effect of stress on the brain. However, no previous study has examined the impact of stress on cognitive function. This article examines the relationship between stress and cognitive function in 82 HIV-negative subjects and 251 HIV-positive subjects. Subjects completed a comprehensive neuropsychological examination, measures of anxiety and depression, and a measure of stressful life events. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 19 publications
2
9
1
Order By: Relevance
“…There are however few studies into the association of these factors with neuro-cognitive impairment in HIV [20]. This study is one of the few that demonstrates this association.…”
Section: Discussionmentioning
confidence: 62%
“…There are however few studies into the association of these factors with neuro-cognitive impairment in HIV [20]. This study is one of the few that demonstrates this association.…”
Section: Discussionmentioning
confidence: 62%
“…It is important to note that it is not only dietary changes that may be important in reducing risk and consequences of disease. Avoiding chronic stress situations and increasing physical activity and exercise (including mental exercise) are also important and can modify the course of cognitive decline and delay mortality 90–93 …”
Section: Inflammation and Brain Functionmentioning
confidence: 99%
“…For example, many studies showed that early life stress exposure was associated with poorer adult cognitive function in memory domains and executive function in healthy and psychopathology populations (Navalta et al, 2006), and individuals who reporting predictive early life stress exhibited poorer processing speed and working memory performance (Saleh et al, 2017). In addition, Pukay-Martin et al (2003) found that, for HIV-positive subjects, stressful life events were related to poor performance on measures of executive function, attention, and processing speed, while positive life events were related to better performance. In addition to behavioral evidence, evidence from neuroimaging study also suggested that, greater activation in brain regions responsible for executive functions accounted for the association between exposure to chronic stress and less use of adaptive coping among adolescents (Reising et al, 2018).…”
Section: Introductionmentioning
confidence: 97%